A review of building factors contributing to building safety performance / Azuin Ramli, Zainal Abidin Akasah, Mohd Idrus Mohd Masirin - Ramli, Azuin; Akasah, Zainal Abidin; Mohd Masirin, Mohd Idrus (2012)
This paper will present a review of literatures pertinent to the building factors contributing to the minimization of safety hazards in built living environment. Review of literatures shows that most property management organisations have not established regular safety inspection and maintenance of existing buildings. This scenario has led to a reduced number of existing buildings related to comfort and safety. Research shows that comfort and safety in a building are critical in order to protect occupants from hazards. Hence, to bridge this gap, this study aims to identify building factors affecting the safety performance of buildings. This research involved a literature search on the identification of the building factors affecting building safety based on the frequency of the factors identified by past researchers. From the mapping matrix, the highest frequency as indicated by most researchers is a means of escape and access that contributes to the minimization of safety hazards of buildings. Meanwhile, factors from each category are also determined. As a result, more effort is necessary to boost and further stimulate action towards a proposed building safety performance assessment framework towards a sustainable built environment.